Thyroid Transcription Factor-1 (TTF-1) expression in lungs metastatic adenocarcinoma from sigmoid primary: a diagnostic pitfall in a 63-year-old man - Yasin, Babar; Ahmad, Muhammad Awais; Qadri, Haseeb Mehmood; Hakeem, Nauman (Journal of the Pakistan Medical Association, 2025)
Thyroid transcription factor 1 (TTF-1), a very sensitive and specific marker for primary lung adenocarcinoma, has been used as a diagnostic marker for distinguishing primary pulmonary neoplasm from adeno-carcinomatous metastasis from other sites, such as the colorectal region. In a few cases, metastases have also been shown to express TTF-1. Here, we present the case of a 63-year-old man who developed metastases to the right lung from metastatic sigmoid adenocarcinoma. The pulmonary secondary lesion was strongly positive for TTF-1. There is a paucity of existing English scientific literature to prove the non-specific nature of TTF-1 expression. This is the first documented case of its kind from Pakistan and probably the sixth case in the world. The versatile expression of tumour markers influences the nature, progression and management of malignancies. Hence, histopathologists need to be aware of this extremely rare occurrence. Keywords: (TTF-1) Thyroid Transcription Factor-1, lung adenocarcinoma, immunohistochemistry, carcinogen marker.